Taurine can Decrease Phosphorylated Tau Protein Levels in Alzheimer’s Model Rats’ Brains - Jahanshahi, M.; Nikmahzar, E.; Gorgani, S. (Kathmandu University Medical Journal, 2021)
Background Microtubule formation is a dynamic process and Tau proteins promote the assembly of tubulin monomers into microtubules. Hyperphosphorylation of some amino acids in tau proteins causes neuron starvation and finally cell death. Taurine is found in the brain and has neuroprotective effects. Objective Since the protective and therapeutic effects of Taurine on phosphorylated tau proteins level in the cerebellum and prefrontal cortex of rats induced by scopolamine have not been studied, we examined these effects. Method Adult male Wistar rats were randomly distributed into nine groups. For two weeks, Taurine-treated rats received different doses of Taurine (25, 50, and 100 mg/kg/ day) before or after scopolamine injection. The phosphorylated tau protein level in the cerebellum and prefrontal cortex was determined by the enzyme-linked immunosorbent assay (ELISA) technique. Result Pretreatment with three doses of Taurine significantly decreased the phosphorylated tau protein level that increased by scopolamine in the prefrontal cortex (p < 0.001), as well as the cerebellum (p < 0.001). Moreover, high-dose administration of Taurine (100 mg/kg/day) after scopolamine injection significantly decreased phosphorylated tau protein level in the cerebellum (p < 0.01), as well as the prefrontal cortex (p < 0.05). However, there was not any significant change in the level of phosphorylated tau protein after Taurine treatment (25 and 50 mg/kg/day) in the cerebellum and prefrontal cortex. Conclusion It can be concluded that Taurine could attenuate the increase in phosphorylated tau protein induced by scopolamine in the brain of rats and usage of Taurine as a pretreatment complement could be more useful in the protection of neurons.